Implementasi Teknologi Informasi dalam Manajemen Administrasi Perkantoran di Sekolah MAS Al-Wasliyah Tembung - Ariana; Andini, Sari; Dwi Putra, Bintang Ridzky; Darmansah, Tengku (Universitas 17 Agustus 1945 Semarang, 2024)
This article discusses the implementation of information technology in office administration management in schools. To support the smooth running of the process Learning certainly requires supporting facilities so that all activities are neatly and efficiently organized. Information technology is here to help the school administration process become more effective and efficient. Of course, it is not only the school administration that will be helped, but communication between teachers, staff and students will improve. Information technology in office administration management also certainly helps manage finances and manage school personnel. The purpose of this article is is to review how the administration system is based information technology to streamline the performance of teaching staff and staff in schools. Method used is descriptive qualitative.